Effects of Vitamin D on House Dust Mite Sensitized Children with Atopic Dermatitis - ÖZEN, AHMET OĞUZHAN; BARIŞ, SAFA (BILIMSEL TIP YAYINEVI, 2017)
Objective: Atopic dermatitis (AD) in studies conducted by the International Study of Asthma and Allergies in Childhood (ISAAC), children aged 6-7 years accounted for less than 2% in Iran, 16% in Japan and Sweden, and 13-14 years in Albania less than 1%, and over 15% in Northern Europe. House dust mite (HDM) sensitivity confers a distinct phenotype in AD. The current study aimed to determine the factors influencing the disease severity in HDM-sensitized AD patients. Materials and Methods: Thirty-three patients with HDM-sensitized AD were enrolled in the study. The medical charts were retrospectively evaluated for complaints, age at admission and diagnosis, delivery, gender, atopy in family, sensitizations, eosinophil counts, immunoglobulin and Vitamin D levels, treatment modalities and response to treatment. Results: The chief complaint was pruritus in 81.8%, rash in 45.5% and dryness in 9.1% of patients. Objective SCORAD (scoring atopic dermatitis) at admission was 45 +/- 15. Severe AD was detected in 21 patients according to their objective SCORAD index. Accompanying allergic diseases were allergic asthma (AA) in 71.9%, allergic rhinitis (AR) in 62.5% and food allergy in 27.3% of the patients. Sixteen (57.1%) patients showed decreased vitamin D levels. When familial atopy, type of delivery, and gender were set as grouping items, age at disease onset and diagnosis, laboratory parameters and objective SCORAD were similar in HDM-sensitized AD patients. On the other hand, patients with low vitamin D levels had significantly low levels of serum IgG and IgA and significantly high levels of specific IgE D1 (p=0.046, p=0.036, p=0.0023 respectively) when compared to those with normal vitamin D levels. In addition, serum vitamin D levels were found to have a strong negative correlation with specific IgE D1 levels (p=0.002, r=-0.617). Conclusion: HDM-sensitized AD has a severe and persistent phenotype. The correlation between low levels of vitamin D and high levels of D1-specific IgE in addition to lower levels of IgG and IgA in vitamin D deficient patients warrants further investigation of immunoregulatory effects of vitamin D in HDM-sensitized AD patients in larger sample sizes.
Keywords: Atopic dermatitis; house dust mite; SCORAD; vitamin D; hypogammaglobulinemia; SERUM IGE LEVELS; RISK-FACTORS; TRANSIENT HYPOGAMMAGLOBULINEMIA; ASTHMA; ECZEMA; CHILDHOOD; SEVERITY; INFANTS; ASSOCIATION; DELIVERY